Utilization of Steepest Ascent and Box-Behnken Design for Determination of Gadolinium in Acetonitrile by Differential Pulse Voltammetry - Santhy Wyantuti; Uji Pratomo; Yeni Wahyuni Hartati; Amelia Shafira; Ari Hardianto; Husein Hernandi Bahti (Universitas Gadjah Mada, 2023)
Gadolinium (Gd) is an important material for advanced technology; hence, the development of a sensitive and efficient alternative for the Gd-detection method to reduce the dependency on complicated and expensive methods has been massively investigated. Furthermore, the combination of differential pulse voltammetry (DPV) and the experimental design to detect Gd provides a simple, effective, and efficient method. In this study, the Steepest Ascent and Box-Behnken designs were chosen to determine the maximum voltammetry responses. The optimum conditions used for this study showed an amplitude modulation of 0.0884 V, potential deposition of 1.4382 V, and deposition time was 60.3615 s with the obtained recovery value, accuracy, and precision values being 98.37, 95.91, and 5.12% in relative standard deviation (RSD), respectively. Meanwhile, the detection and quantization limit values are 3.46 and 11.53 mg/L, respectively. Under optimum conditions, the presence of Gd in acetonitrile is determined in a mixture with Eu and Sm. Based on the results, the DPV method is capable of determining the presence of Gd in acetonitrile.